Pengetahuan tentang Pembelajaran Berbasis Mind Map QR-Code oleh Pendidik - Nelly Yusro; Sakilah; Rian Vebrianto; Arinta Indah Ramadhani (Lembaga Anotero Scientific Pekanbaru, 2021)
This study aims to determine the extent of knowledge about teaching and learning, especially the QR-code mind map by educators. The research method used is an online survey method via google form. The survey method is a research method to obtain data about an existing symptom and seek factual information. The subjects of this study were 16 teachers or educators. The results showed that the educators of the respondents also strongly agreed and were interested in the use of the QR-Code Mind Map for the evaluation process through an IT-based quiz because it provided convenience during the teaching and learning process.